The use of new aceclofenac dosage forms in patients with osteoarthrosis in real-life clinical practice - Lyudmila Ivanovna Alekseeva; E P Sharapova; N G Kashevarova; S G Anikin; T A Korotkova; E M Zaitseva (Современная ревматология)
A new convenient dosage form of aceclofenac (sashet bags) has recently been launched on the Russian market. The powder in a single sashet bag weighs 3 g, which corresponds to 100 mg of the active ingredient per tablet. A prospective study (including evaluation of the effectiveness and safety of the sashet form of aceclofenac in real-life clinical practice) was carried out in 40 outpatients with osteoarthrosis (OA) of the knee and hip joints during 2 weeks. A clear pain relief by 25% vs the beginning of therapy was observed; joint stiffness decreased by 34%; joint function improved by 17%; and the total WOMAC score decreased by 18% by the end of the therapy (262.7±127.7 vs 198.5±111.6; 88.5±42.21vs 57.7±32.6; 789.9±307.2 vs 650.6±242.6 and 1087.7±369.3 vs 886.4±326.0, p<0.05, respectively, in all cases). The results of our surveillance study in real-life clinical practice have shown that sashet aceclofenac rapidly relieves pain and reduces joint stiffness, thus improving the functional condition of joints. Adverse effects related to the gastrointestinal tract were observed in only one (2.5%) patient when using sashet aceclofenac. The drug in this dosage form can be recommended as an effective and safe agent, especially for patients who typically receive non-steroidal anti-inflammatory drugs in liquid forms.